(3GdETQGa Ydi ePGgH GdCTQGas - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s ((3eMeO Hf eMeO MLi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf cJGH GdWgGQI (B: (3CLeY GdYdeGA QVi Gddg Yfge Ydi Cf GdUdGI dG JUM GdG HWgGQI EPG hLO GdSHjd EdjgG s
(3BNQgG (B:s
(3hGNJdahG ajeG GPG bJdJ Ce GdhdO SjOgG agPG ajeG fQGg ebfY Ef TGA Gddg JYGdi hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG ebGHdIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B228s
Keywords: (3CUhd Gdabgs